Hypericum perforatum L.-Mediated Green Synthesis of Silver Nanoparticles Exhibiting Antioxidant and Anticancer Activities - Abdalrahim Alahmad; Armin Feldhoff; Nadja C. Bigall; Pascal Rusch; Thomas Scheper; Johanna-Gabriela Walter (Nanomaterials, 2021)
This contribution focuses on the green synthesis of silver nanoparticles (AgNPs) with a size < 100 nm for potential medical applications by using silver nitrate solution and Hypericum Perforatum L. (St John’s wort) aqueous extracts. Various synthesis methods were used and compared with regard to their yield and quality of obtained AgNPs. Monodisperse spherical nanoparticles were generated with a size of approximately 20 to 50 nm as elucidated by different techniques (SEM, TEM). XRD measurements showed that metallic silver was formed and the particles possess a face-centered cubic structure (fcc). SEM images and FTIR spectra revealed that the AgNPs are covered by a protective surface layer composed of organic components originating from the plant extract. Ultraviolet-visible spectroscopy, dynamic light scattering, and zeta potential were also measured for biologically synthesized AgNPs. A potential mechanism of reducing silver ions to silver metal and protecting it in the nanoscale form has been proposed based on the obtained results. Moreover, the AgNPs prepared in the present study have been shown to exhibit a high antioxidant activity for 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) radical cation, and super oxide anion radical and 2,2-diphenyl-1-picrylhydrazyl. Synthesized AgNPs showed high cytotoxicity by inhibiting cell viability for Hela, Hep G2, and A549 cells.